The Influence of Profitability, Leverage, Liquidity, and ESG Scores on Firm Value of Lq45 Low Carbon Leaders Index Listed Companies for the Period 2021–2024 - Kusuma, Arie Gilang; Sari, Diana (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to examine the extent to which Return on Equity (ROE), Net Profit Margin (NPM), Debt to Equity Ratio (DER), Current Ratio (CR), and Environmental, Social, and Governance (ESG) scores influence firm value, as proxied by Price to Book Value (PBV), among companies listed in the LQ45 Low Carbon Leaders Index during the 2021–2024 period. The study adopts a quantitative approach using panel data regression analysis. The sample consists of 10 companies that consistently reported ESG scores and published both sustainability and financial reports over the four-year observation period. The estimation model employed is the Random Effect Model (REM), selected based on Chow, Hausman, and Lagrange Multiplier tests. The individual influence of each independent variable on firm value is assessed through partial t-tests. The findings indicate that ROE and NPM have a positive and significant effect on firm value, underscoring the importance of profitability in building investor confidence. DER shows a significant negative effect, suggesting that high leverage levels tend to reduce market valuation. Meanwhile, CR and ESG scores exhibit no significant effect on firm value, although ESG scores display a positive directional relationship. This implies that sustainability practices are perceived positively but have yet to become a decisive factor in corporate valuation by the market.